CROSS INFECTION CONTROL AWARENESS OF PAKISTANI DENTISTS FOR COVID-19 PANDEMIC - Hina Zafar Raja; Muhammad Nasir Saleem; Ambreen Shabbir; Maryam Mumtaz; Fizza Tahir (Pakistan Oral & Dental Journal, 2020)
Pandemic of COVID-19 is globally on the rise. Routes of transmission include human to human contact. Dentists are at highest risk of coronavirus infection contraction and dissemination. Due to recent outbreak of this disease, definitive guidelines on this subject are not sufficient for various procedures. Awareness of protective measures for dental practices may reduce the number of new cases within the country. The aim of this study was to evaluate the awareness of cross infection control measures during stage I of pandemic of COVID-19 within dental practices of Pakistan. A cross sectional study based on evidence provided by The School and Hospital of Wuhan University9was conducted during the stage I of spread of coronavirus amongst general dental practitioners of Pakistan. A questionnaire comprising of 10 questions pertinent to the cross-infection protocol for COVID-19 in a dental setting was constructed. Sample size was calculated for registered general dental practitioners of Pakistan. The form was communicated to 200 general dental practitioners all over Pakistan. Out of these, 143 (71.5%) responded. Majority participants showed adequate level of awareness (more than 66%), for protection measures against corona virus COVID-19 in a dental practice. However, few aspects need more emphasis. such as during initial patient interview, temperature evaluation, radiographic records, pre-operative rinses, nature of permissible procedures, surface disinfection, irrigation and drainage methods, to control the chain the infection transmission. Earlier awareness of COVID-19 specific protection measures to health professionals may reduce the number of new diseased cases. Strict adherence to social distancing generally and COVID-19 specific cross infection control measures in a dental setting might help in timely control of this potentially deadly disease.
Keywords: Infection control; Prevention and control; Saliva; Radiography; Dentistry; Diagnosis; Oral